High-stability voltage-resistant NTC (Negative Temperature Coefficient) thermistor and preparation method thereof

The ceramic sheets are prepared by specific ratios of oxides and covered with specific electrode slurry on their surface, which solves the problems of high NTC thermistor resistivity, unstable B value and poor stability, and achieves high stability and good aging resistance.

CN119724784AActive Publication Date: 2025-03-28ZHAOQING JINLONGBAO ELECTRONIC CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411626128.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-28
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing NTC thermistors have problems such as high resistivity, unstable B value, and poor stability and aging resistance.

Method used

The specific ratio of oxides such as Mn3O4, NiO, CuO and other oxides are used as raw materials for ceramic sheets, and the ceramic sheets are prepared through a specific sintering process. At the same time, the surface of the ceramic sheets is covered with electrode slurry composed of silver powder, glass powder and specific organic resin, and the electrode layer is formed by high temperature sintering.

Benefits of technology

The high stability, good aging resistance and voltage resistance of NTC thermistors are achieved, and the key technical problems of existing NTC thermistors are solved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of thermistors, in particular to a high-stability voltage-resistant NTC thermistor and a preparation method thereof. The high-stability voltage-resistant NTC thermistor comprises a ceramic chip serving as a base body and electrode slurry covering the double surfaces of the ceramic chip, the ceramic chip is prepared from the following raw materials in parts by mass: 55 to 70 parts of Mn3O4, 15 to 25 parts of NiO, 10 to 14 parts of CuO, 5 to 10 parts of SiO2, 1 to 3 parts of Al2O3, 0.5 to 2 parts of ZnO and 0.5 to 1 part of Nd2O3. The NTC thermistor prepared in the invention has excellent aging resistance and stability on the premise of good resistivity and B value, has good pressure resistance, has very excellent market prospects, and solves the key technical problems of existing NTC thermistors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermistors, and in particular to a high-stability withstand-voltage NTC thermistor and a preparation method thereof. Background Art

[0002] Thermistors are a type of sensitive components, which are divided into PTC (Positive Temperature Coefficient) thermistors and NTC (Negative Temperature Coefficient) thermistors according to their temperature coefficients. The typical feature of thermistors is that they are sensitive to temperature and show different resistance values ​​at different temperatures. The higher the temperature, the greater the resistance of the PTC thermistor, while the higher the temperature, the lower the resistance of the NTC thermistor. They are both semiconductor devices.

[0003] Among them, NTC thermistor is made of a ceramic body covered with one or more layers of electrode slurry. It has the advantages of large temperature sensitivity coefficient, small size and short response time. It is currently widely used in electronic equipment, automotive accessories, transportation, medical equipment, household appliances, power supply equipment, testing instruments and other fields.

[0004] However, the NTC thermistors in the prior art generally have the technical problems of high resistivity, unstable B value, poor stability and aging resistance. In order to solve this problem, the inventor provides a high-stability withstand voltage NTC thermistor and a preparation method thereof. The NTC thermistor prepared by the present invention has excellent aging resistance and stability, good withstand voltage performance, and has a very excellent market prospect, solving the key technical problems of the existing NTC thermistors. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present invention provides a high-stability withstand-voltage NTC thermistor, which includes a ceramic sheet as a substrate and electrode slurry covering both surfaces of the ceramic sheet.

[0006] As a preferred solution, the raw materials of the ceramic tile include, by weight: 55-70 parts of Mn 3 O 4 , 15-25 parts NiO, 10-14 parts CuO, 5-10 parts SiO 2 , 1 to 3 parts Al 2 O 3 , 0.5 to 2 parts ZnO and 0.5 to 1 part Nd 2 O 3 .

[0007] As a preferred solution, the Mn3 O 4 , NiO, CuO, ZnO and Nd 2 O 3 The mass ratio is (60~65):(20~24):(12~13):(1~1.5):0.8.

[0008] As a preferred solution, the Mn 3 O 4 , NiO, CuO, ZnO and Nd 2 O 3 The mass ratio is (62~64):(22~23):12:1.2:0.8.

[0009] As a preferred solution, the method for preparing the ceramic sheet comprises the following steps: S1: 3 O 4 , NiO, CuO, SiO 2 , Al 2 O 3 , ZnO and Nd 2 O 3 The mixture is mixed evenly and added into a wet ball mill for ball milling to obtain ceramic powder; S2: the ceramic powder after ball milling is mixed with a binder to obtain ceramic particles; S3: the ceramic particles are dry-pressed into sheets and pre-sintered at 800-900°C for 2-3h, then heated to 1100-1200°C and sintered for 4-5h, and a ceramic sheet is obtained after completion.

[0010] As a preferred solution, the ceramic powder D in S1 50 The particle size is 2.5~8μm.

[0011] As a preferred solution, the ceramic powder D in S1 50 The particle size is 5~6.5μm.

[0012] As a preferred solution, the adhesive is polyvinyl acetate.

[0013] As a preferred solution, the mass ratio of the ceramic powder to the binder is (80-100):(1-10).

[0014] As a preferred solution, the mass ratio of the ceramic powder to the binder is (90-100):(5-8).

[0015] As a preferred solution, the electrode slurry comprises, by weight, 60 to 80 parts of silver powder, 5 to 10 parts of glass powder, 1 to 5 parts of oxide, 10 to 25 parts of organic resin, 3 to 5 parts of additives, and 40 to 55 parts of solvent.

[0016] As a preferred solution, the specific surface area of ​​the silver powder is 2 to 8 m 2 / g.

[0017] As a preferred solution, the specific surface area of ​​the silver powder is 4 to 5 m 2 / g.

[0018] As a preferred solution, the mass ratio of the silver powder, glass powder and organic resin is (60-75): (7-9): (15-20).

[0019] As a preferred solution, the mass ratio of the silver powder, glass powder and organic resin is (65-70):8:(18-20).

[0020] As a preferred solution, the oxide is Bi 2 O 3 、ZnO、Ni 2 O 3 , CuO, and CoO.

[0021] As a preferred solution, the oxide is Bi 2 O 3 and CuO.

[0022] As a preferred solution, the Bi 2 O 3 The mass ratio of CuO is (3~4):1.

[0023] As a preferred solution, the organic resin is a composition of acetyl cellulose and polyvinyl pyrrolidone.

[0024] As a preferred solution, the mass ratio of acetyl cellulose to polyvinyl pyrrolidone is (4-5): (2-2.5).

[0025] As a preferred solution, the mass ratio of acetyl cellulose to polyvinyl pyrrolidone is (4.2-4.5):2.

[0026] As a preferred solution, the auxiliary agent is at least one of phosphate esters and aromatic phenol polyoxyethylene ether.

[0027] As a preferred solution, the auxiliary agent is a phosphate ester.

[0028] As a preferred solution, the phosphate ester is at least one of NP phosphate ester, 600 phosphate ester and TSP phosphate ester.

[0029] As a preferred solution, the phosphate ester is NP phosphate ester.

[0030] As a preferred solution, the solvent is at least one of diethylene glycol butyl ether, benzyl alcohol, dimethyl diformate, pineneol, and castor oil.

[0031] As a preferred solution, the solvent is diethylene glycol butyl ether.

[0032] In the present invention, by adopting the above-mentioned specific organic resin selection and matching additives and organic solvents, a carrier flow system with stable adhesion and excellent dispersion can be formed in the silver electrode paste. The specifically selected organic resin can not only provide the required consistency for constructing the carrier flow system in the system, but also further form good silver powder agglomeration sites through the organic resin, and the sites can have a good barrier film through the interaction of additives and solvents, thereby avoiding excessive agglomeration, and then in the process of using the electrode paste, it can be better printed and dispersed on the base ceramic sheet, and form a good connection effect; the existence of this connection effect can ensure the connection strength and stability between the electrode layer and the ceramic sheet during the sintering process, and because of the existence of the barrier film, the exposure of the silver micropowder particles on the surface of the electrode paste can be greatly reduced, thereby ensuring that the surface has more resin components, so that a more uniform and smooth electrode surface is obtained in the process of forming a fixed surface, and then having good voltage resistance.

[0033] As a preferred solution, the glass powder, by weight, comprises: 30 to 45 parts of Bi 2 O 3 , 20-25 parts SiO 2 , 15 to 20 parts Na 2 O, 1-5 parts CaO, 1-3 parts Al 2 O 3 .

[0034] As a preferred solution, the Bi 2 O 3 , SiO 2 , Na 2 O, CaO and Al 2 O 3 The mass ratio is (33~42):(22~24):(16~20):(2~4):(2~3).

[0035] As a preferred solution, the Bi 2 O 3 , SiO 2 , CuO, CaO and B 2 O 3 The mass ratio is 40:23:(17~19):3.5:2.5.

[0036] As a preferred solution, the preparation method of the glass powder includes the following steps: S1: heating to 800-900°C and adding raw materials required for glass powder for smelting to obtain a glass solution; S2: placing the glass solution into 0-5°C cold water for rapid cooling to obtain glass particles, grinding and ball-milling the glass particles, and then drying and passing through a 300-mesh sieve to obtain glass powder.

[0037] As a preferred solution, the preparation method of the electrode slurry includes the following steps: mixing the raw materials required for the electrode slurry, stirring the mixture at a speed of 200 to 300 r / min, and ultrasonically treating the mixture at a power of 400 to 600 w for 3 to 4 hours after stirring, to obtain the electrode slurry.

[0038] The second aspect of the present invention provides a method for preparing the above-mentioned high-stability withstand-voltage NTC thermistor, the preparation method comprising the following steps: flattening the prepared ceramic sheet, then printing electrode slurry on both sides of the ceramic sheet, sintering at high temperature, the thickness of the electrode after sintering is 4 to 6 μm, and the product is obtained after completion.

[0039] As a preferred solution, the sintering temperature of the high temperature sintering is 750-800°C.

[0040] The present invention has the beneficial effects:

[0041] 1. The present invention provides a high-stability withstand-voltage NTC thermistor, which has excellent aging resistance and stability, good withstand-voltage performance, and a very good market prospect, and solves the key technical problems of existing NTC thermistors.

[0042] 2. A high-stability withstand-voltage NTC thermistor provided in the present invention can form a carrier flow system with stable adhesion and excellent dispersion in the silver electrode slurry by selecting a specific organic resin and matching additives and organic solvents; the specifically selected organic resin can not only provide the required consistency for constructing the carrier flow system in the system, but also further form good silver powder agglomeration sites through the organic resin, and the sites can have a good barrier film through the interaction of additives and solvents, thereby avoiding excessive agglomeration, and then in the process of using the electrode slurry, it can be better printed and dispersed on the base ceramic sheet and form a good connection effect; the existence of this connection effect can ensure the connection strength and stability between the electrode layer and the ceramic sheet during the sintering process, and because of the existence of the barrier film, the exposure degree of the silver micropowder particles on the surface of the electrode slurry can be greatly reduced, thereby ensuring that the surface has more resin components, thereby obtaining a more uniform and smooth electrode surface in the process of forming a fixed surface.

[0043] 3. The high-stability withstand-voltage NTC thermistor provided in the present invention has a simple preparation method, easy equipment operation, and readily available raw materials. It can effectively reduce the raw material cost of existing NTC resistors and does not involve complex chemical reactions. In the subsequent large-scale production, it can effectively reduce equipment maintenance and labor costs, and has a very excellent market prospect. DETAILED DESCRIPTION

[0044] The technical solutions in the above invention contents of the present invention will be further described and demonstrated in the form of specific implementation schemes below. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification and should not limit the scope of the claims to be protected by the present invention. All technical products based on the technical solutions described in the invention contents of the present invention should be included in the scope to be protected by the present invention.

[0045] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0046] Example 1

[0047] Embodiment 1 A first aspect provides a high-stability withstand-voltage NTC thermistor, which includes a ceramic sheet as a substrate and electrode slurry covering both surfaces of the ceramic sheet.

[0048] The raw materials of the ceramic tile, by mass, include: 64 parts of Mn 3 O 4 , 22 parts NiO, 12 parts CuO, 6 parts SiO 2 , 2 parts Al 2 O 3 , 1.2 parts ZnO and 0.8 parts Nd 2 O 3 .

[0049] The preparation method of the ceramic sheet comprises the following steps: S1: 3 O 4 , NiO, CuO, SiO 2 , Al 2 O 3 , ZnO and Nd 2 O 3 The mixture is mixed evenly and added into a wet ball mill for ball milling to obtain ceramic powder; S2: the ceramic powder after ball milling is mixed with a binder to obtain ceramic particles; S3: the ceramic particles are dry-pressed into sheets and pre-sintered at 850°C for 2.5 hours, then the temperature is raised to 1200°C and sintered for 4.5 hours to obtain ceramic sheets.

[0050] D of ceramic powder in S1 50 The particle size is 6μm.

[0051] The adhesive is polyvinyl acetate, which is a high-quality polyvinyl acetate product purchased from Wuhan Kangqiong Biotechnology Co., Ltd.

[0052] The mass ratio of ceramic powder to binder is 92:8.

[0053] The electrode slurry, by weight, includes the following raw materials: 68 parts of silver powder, 8 parts of glass powder, 4 parts of oxide, 18 parts of organic resin, 4 parts of additives, and 50 parts of solvent.

[0054] The specific surface area of ​​silver powder is 5m 2 / g, purchased from the corresponding silver micropowder products sold by Huizhou Tenghui Technology Co., Ltd.

[0055] Oxide is Bi 2 O 3 and CuO, the mass ratio of the two is 3:1.

[0056] The organic resin is a composition of acetyl cellulose and polyvinyl pyrrolidone, and the mass ratio of the two is 4.4: 2. The acetyl cellulose is purchased from the acetyl tributyl citrate cellulose resin product sold by Wuhan Kanosi Technology Co., Ltd.; the polyvinyl pyrrolidone is polyvinyl pyrrolidone K90.

[0057] The auxiliary agent is NP phosphate; the solvent is diethylene glycol butyl ether.

[0058] Glass powder, by mass, raw materials include: 40 parts Bi 2 O 3 , 23 parts SiO 2 , 18 parts Na 2 O, 3.5 parts CaO, 2.5 parts Al 2 O 3 .

[0059] The preparation method of glass powder comprises the following steps: S1: heating to 900°C and adding raw materials required for glass powder for smelting to obtain glass solution; S2: placing the glass solution into 5°C cold water for rapid cooling to obtain glass particles, grinding and ball-milling the glass particles, and then drying and passing through a 300-mesh sieve to obtain glass powder.

[0060] The preparation method of the electrode slurry comprises the following steps: mixing the raw materials required for the electrode slurry, stirring the mixture at a speed of 200 r / min, and ultrasonically treating the mixture at a power of 500 w for 4 hours after the stirring is completed.

[0061] The second aspect of this embodiment provides a method for preparing the above-mentioned high-stability withstand-voltage NTC thermistor, the preparation method comprising the following steps: flattening the prepared ceramic sheet, then printing electrode slurry on both sides of the ceramic sheet, sintering at a high temperature of 800°C, the thickness of the electrode after sintering is 5μm, and the product is obtained after completion.

[0062] Example 2

[0063] Embodiment 2 provides a high-stability withstand-voltage NTC thermistor in a first aspect, which includes a ceramic sheet as a substrate and electrode slurry covering both surfaces of the ceramic sheet.

[0064] The raw materials of the ceramic tile, by mass, include: 60 parts of Mn 3 O 4 , 20 parts NiO, 13 parts CuO, 6 parts SiO 2 , 2 parts Al 2 O 3 , 1.5 parts ZnO and 0.8 parts Nd 2 O 3 .

[0065] The preparation method of the ceramic sheet comprises the following steps: S1: 3 O 4 , NiO, CuO, SiO 2 , A l 2 O 3 , ZnO and Nd 2 O 3 The mixture is mixed evenly and added into a wet ball mill for ball milling to obtain ceramic powder; S2: the ceramic powder after ball milling is mixed with a binder to obtain ceramic particles; S3: the ceramic particles are dry-pressed into sheets and pre-sintered at 850°C for 2.5 hours, then the temperature is raised to 1200°C and sintered for 4.5 hours to obtain ceramic sheets.

[0066] D of ceramic powder in S1 50 The particle size is 6μm.

[0067] The adhesive is polyvinyl acetate, which is a high-quality polyvinyl acetate product purchased from Wuhan Kangqiong Biotechnology Co., Ltd.

[0068] The mass ratio of ceramic powder to binder is 92:8.

[0069] The electrode slurry, by weight, includes the following raw materials: 68 parts of silver powder, 8 parts of glass powder, 4 parts of oxide, 18 parts of organic resin, 4 parts of additives, and 50 parts of solvent.

[0070] The specific surface area of ​​silver powder is 5m 2 / g, purchased from the corresponding silver micropowder products sold by Huizhou Tenghui Technology Co., Ltd.

[0071] Oxide is Bi 2 O 3 and CuO, the mass ratio of the two is 3:1.

[0072] The organic resin is a composition of acetyl cellulose and polyvinyl pyrrolidone, and the mass ratio of the two is 4.4: 2. The acetyl cellulose is purchased from the acetyl tributyl citrate cellulose resin product sold by Wuhan Kanosi Technology Co., Ltd.; the polyvinyl pyrrolidone is polyvinyl pyrrolidone K90.

[0073] The auxiliary agent is NP phosphate; the solvent is diethylene glycol butyl ether.

[0074] Glass powder, by mass, raw materials include: 35 parts Bi 2 O 3 , 22 parts SiO 2 , 16 parts Na 2 O, 2 parts CaO, 2 parts Al 2 O 3 .

[0075] The preparation method of glass powder comprises the following steps: S1: heating to 900°C and adding raw materials required for glass powder for smelting to obtain glass solution; S2: placing the glass solution into 5°C cold water for rapid cooling to obtain glass particles, grinding and ball-milling the glass particles, and then drying and passing through a 300-mesh sieve to obtain glass powder.

[0076] The preparation method of the electrode slurry comprises the following steps: mixing the raw materials required for the electrode slurry, stirring the mixture at a speed of 200 r / min, and ultrasonically treating the mixture at a power of 500 w for 4 hours after the stirring is completed.

[0077] The second aspect of this embodiment provides a method for preparing the above-mentioned high-stability withstand-voltage NTC thermistor, the preparation method comprising the following steps: flattening the prepared ceramic sheet, then printing electrode slurry on both sides of the ceramic sheet, sintering at a high temperature of 800°C, the thickness of the electrode after sintering is 5μm, and the product is obtained after completion.

[0078] Comparative Example 1

[0079] The specific implementation of this comparative example is basically the same as that of Example 1, except that the raw materials of the ceramic tile, by mass, include: 80 parts of Mn 3 O 4 , 20 parts NiO, 13 parts CuO, 6 parts SiO 2 , 2 parts A l 2 O 3 .

[0080] Comparative Example 2

[0081] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the raw materials of the electrode slurry, by mass, include: 60 parts of silver micropowder, 20 parts of glass powder, 1 part of oxide, 10 parts of organic resin, 2 parts of additives, and 65 parts of solvent.

[0082] Comparative Example 3

[0083] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the glass powder, in parts by mass, includes: 55 parts of Bi 2 O 3 , 22 parts SiO 2 , 10 parts CuO, 1 part CaO.

[0084] Comparative Example 4

[0085] The specific implementation of this comparative example is basically the same as that of Example 1, except that the organic resin is a composition of acetyl cellulose and polyvinyl pyrrolidone, and the mass ratio of the two is 1.2:3.

[0086] Comparative Example 5

[0087] The specific implementation of this comparative example is basically the same as that of Example 1, except that: D of the ceramic powder in S1 50 The particle size is 2.5μm.

[0088] Performance Evaluation

[0089] 1. Resistivity and B value: The NTC thermistors prepared in the examples and comparative examples were placed in a 25°C thermostat for resistance testing. After measuring their resistance at 25°C, they were placed in a 90°C thermostat for high temperature resistance testing again. The resistivity of the NTC thermistor was calculated from the two resistance values. The average value of 10 tests was recorded in Table 1.

[0090] 2. Aging resistance: The NTC thermistors prepared in the examples and comparative examples were aged for 1000 hours in air at 125°C and 75% humidity, and their resistivity was tested again using the method of performance evaluation 1. The rate of increase of their resistivity relative to the corresponding resistivity in performance evaluation 1 was calculated, and the average value of the measured results of 10 tests was recorded in Table 1.

[0091] Table 1 Performance evaluation test

[0092] Example Resistivity (Ω·□mm) Resistivity change rate (%) Example 1 60.4 0.228 Example 2 61.1 0.241 Comparative Example 1 64.2 0.279 Comparative Example 2 63.3 0.289 Comparative Example 3 62.9 0.288 Comparative Example 4 64.1 0.281 Comparative Example 5 64.7 0.290

[0093] It can be seen from the embodiments of the present invention, the comparative examples and the data results in Table 1 that embodiments 1 and 2 can achieve excellent results in resistivity and aging resistance / stability by adopting the necessary technical solutions defined in the present invention. This is mainly because the specific ceramic sheets and electrode slurry raw material solutions in the present invention enhance the bonding strength between the electrode raw materials and the ceramic sheets and their own dispersion uniformity; while comparative examples 1 to 5 do not adopt the necessary technical solutions, resulting in their corresponding performance tests being significantly worse than embodiments 1 to 3, which further proves the importance of the technical solutions defined in the present invention for its technical effects.

Claims

1. A high stability withstand voltage NTC thermistor, characterized by: The high stability withstand voltage NTC thermistor includes a ceramic chip as a substrate and electrode slurry covering the double surfaces of the ceramic chip; The raw materials of the ceramic tile include, by weight: 55-70 parts of Mn3O4, 15-25 parts of NiO, 10-14 parts of CuO, 5-10 parts of SiO2, 1-3 parts of Al2O3, 0.5-2 parts of ZnO and 0.5-1 parts of Nd2O3; The mass ratio of Mn3O4, NiO, CuO, ZnO and Nd2O3 is (60-65): (20-24): (12-13): (1-1.5): 0.8; The preparation method of the ceramic sheet comprises the following steps: S1: Mn3O4, NiO, CuO, SiO2, Al2O3, ZnO and Nd2O3 are mixed evenly, and added into a wet ball mill for ball milling to obtain ceramic powder; S2: the ceramic powder after ball milling is mixed with a binder to obtain ceramic particles; S3: the ceramic particles are dry-pressed into sheets and then pre-sintered at 800-900°C for 2-3h, and then the temperature is raised to 1100-1200°C and sintered for 4-5h, and the ceramic sheet is obtained after completion; The ceramic powder D in S1 50 Particle size is 2.5-8 μm; The adhesive is polyvinyl acetate; The mass ratio of the ceramic powder to the binder is (80-100):(1-10).

2. The high stability withstand voltage NTC thermistor according to claim 1, characterized in that: The electrode slurry comprises, by weight, 60 to 80 parts of silver powder, 5 to 10 parts of glass powder, 1 to 5 parts of oxide, 10 to 25 parts of organic resin, 3 to 5 parts of auxiliary agent, and 40 to 55 parts of solvent.

3. The high stability withstand voltage NTC thermistor according to claim 2, characterized in that: The specific surface area of ​​the silver powder is 2 to 8 m 2 / g.

4. The high stability withstand voltage NTC thermistor according to claim 3, characterized in that: The mass ratio of the silver powder, glass powder and organic resin is (60-75): (7-9): (15-20).

5. The high stability withstand voltage NTC thermistor according to claim 4, characterized in that: The oxide is at least one of Bi2O3, ZnO, Ni2O3, CuO, and CoO.

6. The high stability withstand voltage NTC thermistor according to claim 5, characterized in that: The oxides are Bi2O3 and CuO; the mass ratio of Bi2O3 to CuO is (3-4):

1.

7. The high stability withstand voltage NTC thermistor according to claim 6, characterized in that: The organic resin is a composition of acetyl cellulose and polyvinyl pyrrolidone; the mass ratio of the acetyl cellulose to polyvinyl pyrrolidone is (4-5): (2-2.5).

8. The high stability withstand voltage NTC thermistor according to claim 7, characterized in that: The auxiliary agent is at least one of phosphate esters and aromatic phenol polyoxyethylene ether.

9. The high stability withstand voltage NTC thermistor according to claim 8, characterized in that: The solvent is at least one of diethylene glycol butyl ether, benzyl alcohol, dimethyl diformate, pineneol and castor oil.

10. A method for preparing a high-stability withstand voltage NTC thermistor according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: flattening the prepared ceramic sheet, then printing the electrode slurry on both sides of the ceramic sheet, sintering at high temperature, and the thickness of the electrode after sintering is 4 to 6 μm.

Citation Information

Patent Citations

  • Silver paste composition and solar cell using same

    CN102763172A

  • Thermal sensitive ceramic material with low resistivity, high B value and negative temperature coefficient and preparation method thereof

    CN104193306A

  • Fast conductivity polymer silver

    CN108779350A

  • Aluminum paste for double-sided PERC back field with high double-sided rate, and preparation method thereof

    CN113393954A

  • Metal slurry, heating circuit, atomizing core, preparation method of atomizing core, and electronic cigarette

    CN113421691A